2000
DOI: 10.1161/01.cir.101.8.856
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Relationship Between Plasma Nitrite and Nitrate Level and Salt Sensitivity in Human Hypertension

Abstract: Background-High salt intake suppresses the effect of nitric oxide (NO) in the peripheral resistance vessels in animal models. We tested the hypothesis that the modulation of endogenous NO is related to salt sensitivity in human hypertension. Methods and Results-Inpatients with essential hypertension (nϭ24) were maintained on a normal-salt diet (12 g/d NaCl)for 3 days, a low-salt diet (2 g), a high-salt diet (20 to 23 g), and a low-salt diet for 7 days. Normotensive subjects (nϭ16) were maintained on the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
149
1
9

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(169 citation statements)
references
References 45 publications
10
149
1
9
Order By: Relevance
“…[20][21][22] However, studies performed in humans in which Abbreviations: BMI, body mass index; BP, blood pressure; NSS, normotensive salt-sensitive subject; NSR, normotensive salt-resistant subject; UK, urine potassium excretion; Una, urine sodium excretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] However, studies performed in humans in which Abbreviations: BMI, body mass index; BP, blood pressure; NSS, normotensive salt-sensitive subject; NSR, normotensive salt-resistant subject; UK, urine potassium excretion; Una, urine sodium excretion.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Studies in patients with essential hypertension have suggested that high salt intake and/or salt sensitivity is associated with impaired endothelial function. [7][8][9] Measurement of flow mediated dilation (FMD) in the brachial artery using ultrasound is noninvasive and is an accurate indicator of NO production. [10][11][12][13] Furthermore, FMD measurement is an accepted index of conduit artery endothelial function, which can serve as an independent predictor of cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma concentrations of asymmetrical dimethylarginine have been reported to be increased in patients with end stage renal disease (Kielstein et al, 2001). More importantly, they are elevated in hyperhomocysteinaemia (Stuhlinger et al, 2001) and in hypertensive patients on a high salt diet (Fujiwara et al, 2000). Therefore our older vegetarian subjects might have elevated plasma concentrations of asymmetrical dimethylarginine as they had high salt intakes as reflected by urinary sodium:creatinine ratios, and they were at risk of hyperhomocysteinemia because of vitamin B12 deficiency (Mezzano et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…These abnormalities reverted to normalcy following salt restriction. Alterations in plasma nitrite and nitrate levels correlated inversely with blood pressure and plasma ADMA levels after salt loading and salt restriction (Fujiwara et al, 2000), suggesting that salt intake modulates NO synthesis via changes in ADMA concentrations. ADMA blocks NO synthesis, which could explain, in part, the role of salt in human hypertension.…”
Section: No and Hypertensionmentioning
confidence: 95%